PERFORMANCE IMPROVEMENT OF GINGER FARMERS IN PEATLAND, KUBU RAYA DISTRICT - Lestary, Septia; Yurisinthae, Erlinda; Maswandi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
The economic value of ginger agricultural commodities has many advantages as a healthy way of life for the society, and this value is reflected in the productivity of ginger farming. When used, peatlands have the potential to significantly boost ginger output, which in turn can help farmers perform more effectively. In the peatlands of Kubu Raya Regency, where ginger is grown, the purpose of this study is to investigate the technical efficacy of ginger farmers and the efforts they make to improve their crops' yields. The choice of locations for the research projects was made deliberatively with consideration given to the proximity of horticulture farmer groups. This study utilized a probability sampling approach and observed 57 representative samples of the farmers who responded to the survey. The software program known as FRONTIER 4.1 is used to aid in the stochastic frontier analysis (SFA) approach of data analysis. Based on the results of the study, the t value for the variable land area was 6.71 > 2.07 and the t value for the seed variable was 5.70 > 2.07 indicating that these two variables had a considerable influence on ginger yield. This data means that the technical efficacy of ginger farmers and the efforts they make can increase ginger yields. With this, it is important for farmers to pay attention to the performance given to ginger plants planted to obtain increased income.